2020
DOI: 10.1111/tmi.13517
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and associated risk factors of Helicobacter pylori infection in the Wuwei cohort of north‐western China

Abstract: Objectives To evaluate the prevalence of Helicobacter pylori infection and risk factors and to serotype the strains in Wuwei, located in north‐western China, which has a high incidence of gastric cancer. Methods Helicobacter pylori infection was analysed in 21 291 adults by 14C‐urea breath test, and H. pylori antibody were detected in 9183 serum samples by latex immunoturbidimetric method. The correlation of H. pylori infection with demographic–economic, lifestyle factors and medical history among the particip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
25
3
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 41 publications
6
25
3
5
Order By: Relevance
“…For H. pylori- infected adult patients in the family, eradication therapy is recommended unless competing considerations exist. 1 13 Recent studies on the genotyping of infected persons also show that type I H. pylori strains (CagA and VacA positive) are the major type of H. pylori infection in Chinese residents, 65 103 104 and it induces severer inflammation, gastric mucosal lesions and are more prevalent in patients with GC than type II (CagA and VacA negative) strains. This is also supported by population-based studies and confirmed by basic science research experiments.…”
Section: Resultsmentioning
confidence: 99%
“…For H. pylori- infected adult patients in the family, eradication therapy is recommended unless competing considerations exist. 1 13 Recent studies on the genotyping of infected persons also show that type I H. pylori strains (CagA and VacA positive) are the major type of H. pylori infection in Chinese residents, 65 103 104 and it induces severer inflammation, gastric mucosal lesions and are more prevalent in patients with GC than type II (CagA and VacA negative) strains. This is also supported by population-based studies and confirmed by basic science research experiments.…”
Section: Resultsmentioning
confidence: 99%
“…High income and higher educational levels are associated with a decrease in the prevalence of H. pylori gastritis [12,13]. Additionally, age, occupation, the type of drinking water used, consumption of fruits, vegetables, or fried food are also independent risk factors for H. pylori infection [14][15][16]. Smoking and alcohol consumption were also found to be independently positively associated factors [17].…”
Section: Introductionmentioning
confidence: 96%
“…However, our results did not support this conclusion. HP virulence factors vary depending on the geographical distribution, and not all HPs can produce these virulence proteins ( 45 ). Although the dominant HP isolates are CagA gene-positive in East Asia ( 45 , 46 ), some infected individuals in our study may carry CagA gene-negative strains, and whether the negative strains affect the stability of plaques is still unclear, which may cause inaccurate results.…”
Section: Discussionmentioning
confidence: 99%
“…HP virulence factors vary depending on the geographical distribution, and not all HPs can produce these virulence proteins ( 45 ). Although the dominant HP isolates are CagA gene-positive in East Asia ( 45 , 46 ), some infected individuals in our study may carry CagA gene-negative strains, and whether the negative strains affect the stability of plaques is still unclear, which may cause inaccurate results. In addition, we speculated that the bacterial content in the plaque potentially affects plaque stability, and when the bacteria are present in small amounts, they will not affect the stability of plaques.…”
Section: Discussionmentioning
confidence: 99%